Perhitungan Sumberdaya Nikel Laterit Menggunakan Metode Inverse Distance Weighting Pada PT Genba Multi Mineral Di Kabupaten Morowali - YAZID, LM YAZID AMSAH; Amzah, La Ode Muh Yazid; Noor, Moh Khaidir; Surianti; Malim, Anna Irada La Ode (JNANALOKA, 2023)
Resource estimation plays a significant role in determining the quantity and quality of a deposit. In nickel laterite mining, estimation is needed to be able to calculate resources before the mining process takes place. This research was conducted to determine the nickel laterite resources at PT Genba Multi Mineral. In this research, the determination of nickel laterite resource estimation using the Inverse Distance Weighting (IDW) method. Based on the estimation of nickel laterite resources using the IDW method. The estimation of nickel laterite resources was carried out in the saprolite zone with the Cut of Grade (COG) used, namely Ni content ≥ 1.6% with a density of 1.5 tons/m3 obtained a resource tonnage of 233,738 tons with an average Ni content of 1.81%.